Commerce Versus Commentary: Gripe Sites, Parody, and the First Amendment in Cyberspace - Jacqueline D. Lipton (Washington University Law Review, 2006)
The Global Online Freedom Bill of 2006 emphasizes the importance of freedom of speech on the Internet as a fundamental human right. However, the backbone of the World Wide Web, the Internet domain name system, is a poor example of protecting free speech, particularly in terms of the balance between speech and commercial trademark interests. This is apparent from the manner in which the legislature and the judiciary deal with cases involving Internet gripe sites and parody sites. The lack of a clear consensus on the protection of free speech in these contexts is troubling, and can be found in a number of recent cases involving situations such as use of the peta.org domain name for a parody site on the activities of People for the Ethical Treatment of Animals; use of bosleymedical.com for a gripe site about the practices of the Bosley Medical Institute; and use of a misspelling of the Reverend Jerry Falwell’s last name (fallwell.com) for a website critical of the Reverend’s viewpoints on homosexuality. This Article examines how trademark law has come to trump freedom of expression under the domain name system and makes recommendations for regulatory reform to ensure a better balance of rights in the future. In particular, it suggests the development of presumptions against trademark infringement in cases clearly involving criticism or parody of a trademark holder in cyberspace.
Keywords: Cybergriping; Parody; Trademark infringement; Domain names; Freedom of speech; united States Constitution